Prediction of the development and susceptibility to acute mountain sickness (AMS) by monitoring oxygen saturation (SpO2) - literature review - Karol Mazur; Dominik Machaj; Sandra Jastrzębska; Alicja Płaczek; Dominika Mazur (Kazimierz Wielki University, 2020)
The hypoxia is the main cause of altitude sickness, that usually starts from the benign form - acute mountain sickness (AMS), that being untreated can progress to the life-threatening states, like high altitude pulmonary edema (HAPE) and high altitude cerebral edema (HACE). The aim of this study was to evaluate the role of monitoring oxygen saturation in prediction of the of the development and susceptibility to acute mountain sickness (AMS). Our study material consisted of publications, which were found in PubMed, ResearchGate and Google Scholar databases. The first step was to find proper publications from the last 25 years .The second step was to carry out an overview of the found publications. Based on this criteria, six publications have been qualifed for the study. There is strong relationship between development and susceptibility to acute mountain sickness (AMS) and hypoxia. But this topic is not fully understood and needs to be better researched. Monitoring oxygen saturation could prevent from the development and predcit the susceptibility to AMS. Pulse oxymetry could be also the indicator of adequate or inadequate acclimatization and high altitude performance.